2020
DOI: 10.1158/2326-6066.cir-20-0020
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Nonmutated Neoantigens Induced in Recurrent and Future Tumors

Abstract: is a founder and equity holder of Sebastian Biopharma that holds intellectual rights for the neoantigen induction approach described in this study.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A20 lymphoma was extensively tested as a target for decoy-based strategies in our previous studies. 17 , 18 , 32 Within 24 h, C-STAT3DPROTAC dose-dependently reduced total STAT3 levels, with inhibition reaching maximum of 85% at 2 μM concentration ( Figure 4 A). In contrast, the effect of negative control treatment using an equimolar mixture of unconjugated STAT3D ODN and thalidomide was negligible ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 98%
“…A20 lymphoma was extensively tested as a target for decoy-based strategies in our previous studies. 17 , 18 , 32 Within 24 h, C-STAT3DPROTAC dose-dependently reduced total STAT3 levels, with inhibition reaching maximum of 85% at 2 μM concentration ( Figure 4 A). In contrast, the effect of negative control treatment using an equimolar mixture of unconjugated STAT3D ODN and thalidomide was negligible ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 98%
“…TAP downregulation promoted an antitumor immune response in mice, inhibiting tumor growth in the absence of measurable toxicity. Based on the antitumor response elicited in cancer cells upon TAP downregulation, Garrido and coworkers 16 further investigated a novel anti-tumor strategy of vaccination against TEIPP induced by TAP downregulation. To this end, the authors took advantage of a CpG oligonucleotide as the targeting moiety for a TAP-specific siRNA.…”
Section: Enhancing Anti-cancer Immunitymentioning
confidence: 99%
“…The authors concluded that vaccination against TEIPP antigens is effective at enhancing the antitumor response elicited against tumor cells treated with the Nucl-TAP aptamer conjugate to induce TEIPP. 16 Given the limited success of current immunotherapies against solid tumors, combinatorial and synergistic therapies might be required to fight the most difficult-to-treat tumors. A recent study by Zhang et al 17 set out to combine different aptamer-siRNA chimeras targeting different tumor cell regulatory pathways to enhance immunotherapy.…”
Section: Enhancing Anti-cancer Immunitymentioning
confidence: 99%
“…[ 2 ] Non‐synonymous mutations mainly include point mutations, frameshift mutations, splice‐site mutations and fusion mutations, and a higher burden of non‐synonymous mutations can enhance the immunogenicity of neoantigens. [ 3 ] Point mutations neoantigens are derived by single‐nucleotide variants (SNVs), including KRAS G12V/D, p53 R175H, etc. [ 4 ] Differently, frameshift peptides (FSPs) come from insertion or deletion (INDEL) of base pair in the genome.…”
Section: Introductionmentioning
confidence: 99%